EVA Conference Berlin 2025. Electronic Media and Visual Arts (diségno, 2025)
From March 12-14, the Fraunhofer Heinrich Hertz Institute hosted the EVA Conference Berlin 2025, focusing on Electronic Media and Visual Arts (fig. 1). This 28th edition of the conference series brought together scientists and practitioners from diverse disciplines to discuss current developments in digital media and visual arts. [read more]